2020
DOI: 10.1042/bsr20200262
|View full text |Cite|
|
Sign up to set email alerts
|

High-glucose environment accelerates annulus fibrosus cell apoptosis by regulating endoplasmic reticulum stress

Abstract: Diabetes mellitus (DM) is an important risk factor of intervertebral disc degeneration. However, how DM affects annulus fibrosus (AF) biology remains unclear. The present study was aimed to investigate the effects and mechanism of high glucose on AF cell biology. Rat AF cells were cultured in baseline medium and culture medium with 0.2 M glucose. The inhibitor 4-PBA was added along with the high glucose culture medium to study the role of endoplasmic reticulum (ER) stress in this process. Compared with the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…ATF4 promotes the induction of ER stress (ERS)-induced apoptosis, and its activation is intrinsically associated with the phosphorylation of eIF2α involving many stress signaling pathways ( Wek et al, 2006 ). Excessive ERS can activate Caspase12 precursors on the ER, further activate Caspase3, and perform an apoptotic response ( Zhao et al, 2010 ; Pang et al, 2020 ). In our study, TNF-α increased the Caspase3 expression and apoptosis, which was aggravated by BTd supplement.…”
Section: Discussionmentioning
confidence: 99%
“…ATF4 promotes the induction of ER stress (ERS)-induced apoptosis, and its activation is intrinsically associated with the phosphorylation of eIF2α involving many stress signaling pathways ( Wek et al, 2006 ). Excessive ERS can activate Caspase12 precursors on the ER, further activate Caspase3, and perform an apoptotic response ( Zhao et al, 2010 ; Pang et al, 2020 ). In our study, TNF-α increased the Caspase3 expression and apoptosis, which was aggravated by BTd supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in a different context showed that constant glucose availability and lactate removal alongside a likely oversupply of growth factors through routine medium changes does not reflect the in vivo situation of cells, especially not those of NP cells ( Cantor et al, 2017 ). Nutrient concentrations of commonly used media often differ from those in human plasma ( Cantor et al, 2017 ) and are frequently high in glucose (4.5 g/L), yet many stem or stromal cells, including those of the NP, perform better under low glucose conditions ( Saki et al, 2013 ; Liu et al, 2020 ; Pang et al, 2020 ). Low glucose medium (1 g/L, 5.5 mM), including the glucose contribution from 10% FBS, is not yet considered pre-diabetic (10 mM) ( Johnson et al, 2008 ; Wuertz et al, 2008 ; Turner et al, 2016 ; Lyu, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In AF cells, high glucose stimulates ERS and increases the gene and protein expression of CHOP, ATF6, and GRP78, which are the important factors in ERS. In addition, the apoptosis of AF cells is also increased ( 126 ). Due to the high blood glucose level, the chemotaxis of leukocytes is decreased, and the outcome of IDD surgery is often worse ( 127 ).…”
Section: Activation Of Ers Contributes To Idd Pathological Developmentmentioning
confidence: 99%
“…Consistently, 4-PBA can inhibit tension-induced IDD development, as indicated by reduced apoptosis, ameliorated ERS, and decreased ROS generation in AF cells ( 119 ). 4-PBA can also inhibit high glucose-induced apoptosis by inhibiting ERS in AF cells ( 126 ). TUDCA, a hydrophilic bile acid, has been reported to inhibit ERS-induced catabolism and reduce excessive mechanical compression-stimulated apoptosis in NP cells ( 133 , 134 ).…”
Section: Ers May Become the Potential Therapeutic Target To Prevent I...mentioning
confidence: 99%